Genetically predicted circulating levels of copper and zinc are associated with osteoarthritis but not with rheumatoid arthritis. Issue 7 (July 2021) - Zhou, J.; Liu, C.; Sun, Y.; Francis, M.; Ryu, M.S.; Grider, A.; Ye, K.
Summary: Objective: Osteoarthritis (OA) and rheumatoid arthritis (RA) are both debilitating diseases that cause significant morbidity and disability globally. This study aims to investigate the causal effects of varying blood levels of five minerals -- iron, zinc, copper, calcium, and magnesium, on OA and RA. Design: We performed two-sample Mendelian randomization (MR) analyses to assess the associations of five circulating minerals with OA and RA. Single nucleotide polymorphisms (SNPs) serving as genetic instruments for the circulating mineral levels were selected from large genome-wide association studies of European-descent individuals. The associations of these SNPs with OA and RA were evaluated in UK Biobank participants. Multiple sensitivity analyses were applied to detect and correct for the presence of pleiotropy. Results: Genetically determined copper and zinc status were associated with OA, but not with RA. Per standard deviation (SD) increment in copper increases the risk of OA (OR = 1.07, 95% CI: 1.02–1.13) and one of its subtypes, localized OA (OR = 1.08, 95% CI: 1.03–1.15). Per SD increment in zinc is positively associated with risks of OA (OR = 1.07, 95% CI: 1.01–1.13), generalized OA (OR = 1.18, 95% CI: 1.05–1.31), and unspecified OA (OR = 1.21, 95% CI: 1.11–1.31). Additionally, per SD increment in calcium decreases the risk of localized OA (OR = 0.83, 95% CI: 0.69–0.98). Conclusions: Genetically high zinc and copper status were positively associated with OA, but not with RA. Given the modifiable nature of circulating mineral status, these findings warrant further investigation for OA prevention strategies.